For All Good Reasons: Role of Values in Organizational Sustainability - Florea, Liviu; Cheung, Yu Ha; Herndon, Neil C. (2013)
Management practices are at the heart of most organizations’ sustainability efforts. Despite the importance of values for the design and implementation of such practices, few researchers have analyzed how human values, particularly ethical values, relate to human resource management practices in organizations. The purpose of this conceptual paper is to integrate scholarship on organizational sustainability, human resource practices, and values in delineating how four specific values—altruism, empathy, positive norm of reciprocity, and private self-effacement—support effective human resource practices in organizations. This set of distinct values has sustainability implications, global relevance, and ethical significance. Propositions that indicate relationships among these values, human resource practices, and organizational sustainability, as well as the effects of the resource-based view to potentiate these relationships, are developed. This analysis suggests that ethical and multicultural values are important for planning and implementing effective management practices and organizational sustainability.
Keywords: Resource-based view; Private self-effacement; Positive norm of reciprocity; Organizational sustainability; High-performance human resource management practices; Empathy; Culture-free personal values; Altruism